FDI in the CEEC's and the theory of real options: An empirical assessment - Carlo Altomonte (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
Building on the empirical evidence resulting from a newly developed database of foreign direct investment (FDI) operations in the countries of Central and Eastern Europe (CEECs), panel data techniques are used to show that, at the sector level, a consistent modelling of FDI flows needs to take into account not only the determinants traditionally considered by the literature, including the recent developments on gravity models, but also variables linked to the institutional environment in which the FDI is undertaken. The inclusion of these variables, affecting the risk and the uncertainty of the FDI operation, is in line with the main findings of the real option theory of investments, whose implications are here empirically tested with success.
Keywords: C23; D81; F15; F21; P20; 330; panel data; real option theory; gravity models; FDI; transition economies